Methodological aspects of the study of quasiisoentropic air compression in a flat supersonic inlet device of a power plant with GTE - Artem Khorokhordin; Mykhailo Mitrakhovych (Авіаційно-космічна техніка та технологія, 2024)
The subject of the research is the parameters and characteristics of the supersonic part of the supersonic input device of external compression, namely: the coefficient of preservation of the full pressure of the supersonic part of the flat supersonic input device of external compression, the intensity of oblique and straight jumps of the seal, the total angle of inclination of the braking surfaces, and the length of the straight jump of the seal of the flat supersonic input external compression device from the calculated number M when changing the number of braking surfaces. The object of this research is the supersonic part of the supersonic input device for external compression. The purpose of this work is to study the quasi-isentropic system of oblique compression jumps in the supersonic part of the supersonic input device for external compression to form a preliminary model of the supersonic input device for external compression. To achieve this goal, the following tasks were solved: modeling of the flow in the supersonic part of the supersonic input device of external compression was carried out when the number of M in the supersonic range from 1.5 to 5.0 and the number of braking surfaces from 1 to 60 was changed; the calculation of the main parameters and geometric characteristics of the supersonic part of the supersonic external compression input device was carried out; a criterion for determining the transition to quasi-isentropic compression in the supersonic part of the supersonic input external compression device was proposed. When studying the main characteristics of the supersonic part of the supersonic input device for external compression, a numerical experiment method was used using the gas-hydraulic theory of shock waves with an adiabatic index of 1.41. The influence of the fuselage on the operation of the supersonic part of the supersonic input device was not considered. The results of supersonic flow modeling showed that the main characteristics, namely the coefficient of preservation of full pressure, the intensity of the oblique jump of the seal, the direct jump of the seal, the total angle of inclination of the braking surfaces, and the length of the direct jump from the number M when the number of braking surfaces is changed, practically do not change when the number of braking surfaces is increased by more than 20, that is, the compression process becomes quasi-isentropic, and this number (more than 20 braking surfaces) can be proposed as a criterion for transitioning to quasi-isentropic compression. The scientific novelty and practical significance of the research results lies in the fact that new data were obtained regarding the characteristics of the supersonic part of the supersonic input device under external compression when the number of M, number of braking surfaces, and height of the input is changed. Recommendations on the justification of the choice of the calculated number M and entrance height for the creation of a preliminary model of the supersonic entrance device for external compression.